Measuring overt and covert responses in videogame context - Teixeira, Tiago Barroso (2015)
The videogame industry is huge and is in continuous growth. Given this, there is interest in empirical studies that enlighten different concepts in the research field of gaming experience like engagement, immersion, presence, arousal or flow. It is relevant to understand which technology or instruments can be used to identify the desired indicators to access gaming experience in a product testing situation. The main focus of the work here presented is to compare the gaming experience felt by players with different skill levels with the object of this study – FIFA14. To access the gaming experience of the players I used different instruments like the iGEQ (in-game experience questionnaire), self-assessment manikin scale, eye tracking technology and electro dermal activity. Additionally the effectiveness of an in-game brand placement was tested, with the help of eye tracking technology and a questionnaire. There was a total of 41 participants in the empirical tests playing FIFA14. They played three skill challenges and one match against a computer controlled opponent. While they were performing this, their gaze behavior, pupil dilation and electro dermal activity were recorded. Additionally they were asked to answer a questionnaire. The results showed that the method used to form groups based on the skill of the participant was a success. Low skilled participants appeared to experience more arousal than the higher skilled ones. However high skilled participants revealed to have a more positive experience playing FIFA14 than the low skilled ones. Further evidences were not so clear, but still interesting for the theoretical understanding and practical relevance of the named concepts.